FINANCIAL RESOURCES OF THE SYSTEM OF SOCIAL SECURITY OF UKRAINE - Solodzhuk , T.V. (The actual problems of regional economy development, 2018)
Using the system approach in the article, the essence of the concept "financial resources of social insurance" was investigated. It is analyzed the formation of Ukraine’s social insurance financial resources and the influence of their structure on the budgets of targeted social insurance funds efficiency is carried out. The effectiveness of the insurance funds' budgets is assessed. The methodical tools for assessing the effectiveness of the social insurance system of Ukraine functioning and the scientific provisions for improving its effectiveness were further developed.